2019
DOI: 10.1371/journal.pgen.1008189
|View full text |Cite
|
Sign up to set email alerts
|

Host-dependent nitrogen recycling as a mechanism of symbiont control in Aiptasia

Abstract: The metabolic symbiosis with photosynthetic algae allows corals to thrive in the oligotrophic environments of tropical seas. Different aspects of this relationship have been investigated using the emerging model organism Aiptasia . However, many fundamental questions, such as the nature of the symbiotic relationship and the interactions of nutrients between the partners remain highly debated. Using a meta-analysis approach, we identified a core set of 731 high-confidence symbiosis-associ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
159
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(188 citation statements)
references
References 42 publications
11
159
1
Order By: Relevance
“…Longstanding work has shown that symbionts in hospite are generally nitrogen limited as studies have demonstrated that supplemental ammonium increases symbiont density (e.g., Falkowski, Dubinsky, Muscatine, & McCloskey, 1993;Muller-Parker, McCloskey, Hoegh-Guldberg, & McAuley, 1994;Muscatine, Falkowski, Dubinsky, Cook, & McCloskey, 1989), photosynthesis, and chlorophyll content (Hoegh-Guldberg & Smith, 1989), suggesting nitrogen limitation controls symbiont proliferation. Recent work by Cui et al (2019) integrating metabolomics and transcriptomics not only supports this but further suggests that under heat stress, decreased ammonium assimilation by the host results in more ammonium availability to the symbiont, leading to increased symbiont division and the intensification of the disturbance between the two partners.…”
Section: Nutrient Recycling In Hospitementioning
confidence: 90%
“…Longstanding work has shown that symbionts in hospite are generally nitrogen limited as studies have demonstrated that supplemental ammonium increases symbiont density (e.g., Falkowski, Dubinsky, Muscatine, & McCloskey, 1993;Muller-Parker, McCloskey, Hoegh-Guldberg, & McAuley, 1994;Muscatine, Falkowski, Dubinsky, Cook, & McCloskey, 1989), photosynthesis, and chlorophyll content (Hoegh-Guldberg & Smith, 1989), suggesting nitrogen limitation controls symbiont proliferation. Recent work by Cui et al (2019) integrating metabolomics and transcriptomics not only supports this but further suggests that under heat stress, decreased ammonium assimilation by the host results in more ammonium availability to the symbiont, leading to increased symbiont division and the intensification of the disturbance between the two partners.…”
Section: Nutrient Recycling In Hospitementioning
confidence: 90%
“…A growing understanding of the metabolic hostsymbiont relationship has encouraged the use of methods that allow the measuring of these dynamics, such as metabolomics (Cui et al, 2019;Matthews et al, 2017) or NanoSIMS (Krueger et al, 2018). Recent studies have increasingly been combining coral and Symbiodiniaceae responses in their hypothesis testing.…”
Section: The Holistic Holobiontmentioning
confidence: 99%
“…Recent studies have increasingly been combining coral and Symbiodiniaceae responses in their hypothesis testing. A growing understanding of the metabolic hostsymbiont relationship has encouraged the use of methods that allow the measuring of these dynamics, such as metabolomics (Cui et al, 2019;Matthews et al, 2017) or NanoSIMS (Krueger et al, 2018). These have shown that the metabolic balance between the two partners is not only sensitive to environmental stressors but specifically fine-tuned (Cui et al, 2019;Matthews et al, 2017;Nielsen, Petrou, & Gates, 2018).…”
Section: The Holistic Holobiontmentioning
confidence: 99%
See 1 more Smart Citation
“…Under elevated seawater temperature, the uptake of both nitrate and ammonium is reduced in some coral species (Godinot et al 2011). Alternatively, because coral hosts and symbionts recycle nitrogen and symbiont autotrophy can be maintained by heterotrophic feeding during elevated seawater temperature (Wang and Douglas 1998;Ezzat et al 2016;Tremblay et al 2016), symbiont δ 15 N values may reflect hostdependent regulation of nitrogen available to the symbiont (Falkowski et al 1993;Cui et al 2018).…”
Section: Nitrogen Isotope Ratios Provide Insight Into Changes In Coramentioning
confidence: 99%